THE EFFECT OF TELELACTATION SERVICES ON BREASTFEEDING OUTCOMES: SCOPING REVIEW - Ekacahyaningtyas, Martina (Universitas Aisyah Pringsewu, 2024)
Breast milk is considered the best food for babies as it provides the most suitable source of nutrition and has a complete nutritional composition that supports their growth and development. Counseling is provided to support successful breastfeeding practices. With the advancement of technology in the 4.0 era, online media can be used for counseling purposes. Telehealth-based lactation counseling also known as telelactation, is provided to help improve breastfeeding practices. This study aimed to review the evidence base regarding the influence of telelactation services on breastfeeding outcomes. The method used is a scoping review using PRISMA, to identify articles published during the last 5 years (2019-2023). Data collection was obtained through the database sources Science Direct, ProQuest, Scopus, Cinahl, and PubMed. The keywords used in searching for articles are